ADL and Cognitive Function in Chinese Elderly: Mediating Role of Social Participation and Moderating Role of Intergenerational Support - Li W; Xin D; Feng X; Li Y; Zhu W; Xu J; Yin S (Journal of Multidisciplinary Healthcare)
Wanling Li,1,2,* Dinuo Xin,2,* Xiaofang Feng,2 Yueqin Li,2 Wenjuan Zhu,2 Jiajia Xu,2 Shiyu Yin1 1Department of Nursing, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 2Department of Nursing, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Third Hospital of Shanxi Medical University, Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shiyu Yin, Department of Nursing, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095 Jiefang Avenue, Wuhan, Hubei, 430030, People’s Republic of China, Tel/Fax +86-18834896110, Email 1538746173@qq.com Jiajia Xu, Department of Nursing, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Third Hospital of Shanxi Medical University, Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China, Tel/Fax +86-351-8379512, Email xujiajia392@163.comPurpose: This study aimed to explore the relationship between activities of daily living (ADL) and cognitive function in Chinese elderly, and to analyze in depth the mediating and moderating roles of social participation and children’s intergenerational support in this relationship, in order to provide a reference basis for delaying cognitive decline in the elderly.Patients and Methods: Based on data from the 2020 wave of China Health and Retirement Longitudinal Survey (CHARLS 2020), this study included 5612 subjects aged 60 years and older, and extracted main variables such as demographic information, ADL, social participation, cognitive function, and children’s intergenerational support. Descriptive statistics and Pearson’s correlation analysis in SPSS 27.0 were used to analyze the relationship between the main variables, and regression and Bootstrap analysis in SPSS 27.0 PROCESS macro (Model 4 and Model 14) were further used to analyze the mediating and moderating effects.Results: Among Chinese elderly, ADL significantly positively correlated with social participation (r = 0.086, P < 0.001) and cognitive function (r = 0.193, P < 0.001), and social participation significantly positively correlated with cognitive function (r = 0.144, P < 0.001). Social participation partially mediated the relationship between ADL and cognitive function (β = − 0.202, P < 0.001), accounting for 5.74% of the total effect. Moreover, children’s intergenerational support negatively moderated the relationship between social participation and cognitive function (β = − 0.182, P < 0.001). Thus, a moderated mediation model was developed.Conclusion: ADL can affect cognitive function directly or indirectly through social participation in elderly. Furthermore, children’s intergenerational support plays a negative moderating role in this mechanism. Therefore, governments, hospitals, communities, and families should provide personalized intervention strategies for elderly to delay cognitive decline and promote healthy aging through early prevention of ADL impairment, promotion of social participation, and optimization of family support.Keywords: activities of daily living, cognitive function, elderly, social participation, intergenerational support